The Final Choice: Death or Transcendence? by Michael Grosso - Dossey, Larry (Journal of Scientific Exploration, 2018)
“In reality, there are no final choices,” says academic philosopher Michael Grosso, author of The Final Choice. “As long as we are conscious beings we are free to keep making new and hopefully better choices” (p. xiii). With this up-front qualification, Grosso embarks on an inspiring examination of how we might make new and better choices as a species, and why it is imperative for us to do so if we are to survive and thrive. Here is the motif that informs Grosso’s narrative in The Final Choice: What at bottom drives all living things? The goal of life seems to be more life, self-replication with infinite variations. …The tendency among mammals, and humans in particular, is toward greater mobility, freedom and detachment from the environment. Human life is especially mobile and already has begun to move beyond the planetary habitat to explore outer space habitats. If the goal of life is more life — in a word, survival — the function of our nonphysical psychic potential may be to mediate survival of bodily death…. If the goal of life is more life, higher, freer, more complex forms of life, then our psychic potentials represent the power of life transcending its biological template. Psi is the wedge of life driving against the constraints of physical reality, against the boundaries of time and space. Psi is the medium in which new forms of life carry us beyond the boundaries of physical environment [p. 11]. Grosso considers the near-death experience (NDE) as “perhaps the most important psychological phenomenon of the 20th century, as shocking and counter-intuitive as quantum mechanics….” He adds, “We have millions of repetitions of the near-death experience … and can study and analyze it with the tools of science and other intellectual disciplines. The NDE experientially provides access to a greater mental, indeed spiritual sphere of being” (p. xii). Grosso raises the possibility that, with environmental collapse now in sight, a global version of a near-death experience may be forming, analogous to a human approaching death. It’s the sort of thing one might predict from the life force, whose evolutionary vector is toward more life, more survival, a future. And just as individual NDEs result in a radical transformation and reorientation of the person undergoing them, our planetary citizenry, en masse, may similarly change channels in our priorities, values, and how we live our lives. If so, we just might squeak by. (I’m reminded of a hallway conversation I once had with the late physicist David Bohm. I asked him his opinion of the future of humankind: “Do you think we’ll make it?” He paused, thinking intently, then said, “Yes. Barely.”) Grosso’s stated goal in The Final Choice is “to create a new, fact-based mythology of transcendence.” For him, this entails two aspects of transcendence: “the survival of consciousness after death and, no less momentous, the idea of an extended transpersonal mind. Pim van Lommel (2010) calls it ‘endless consciousness’ or following the Upanishads, Erwin Schrödinger (1963) referred to the one mind. Later, Larry Dossey (2013) coined the phrase ‘nonlocal mind’ and has described in detail how we can make sense of being part of the one mind in his book of that title” (pp. xi-xii). (Full disclosure: whether Grosso’s favorable nod to my work influences this review is for the reader to decide.) Grosso employs a nonlocal model of consciousness — consciousness that is not localized or confined to specific points in space, such as brains or bodies, nor to specific points in time, such as the present. Nonlocal mind is Mind at Large, as Aldous Huxley and others have called it. Survival follows, because mind that is boundless or nonlocal with respect to time is seemingly eternal or immortal; and mind nonlocal or boundless with respect to space is omnipresent. So the critical question becomes: What is the evidence that mind is nonlocal? Grosso shows how consciousness variously manifests nonlocally, making the case for Mind at Large, a universal or unitary mind of which each individual mind is a part. Grosso wrote the first edition of The Final Choice in 1985. This revised edition takes into account a plethora of findings by consciousness researchers that have emerged in the nearly three decades separating the two editions.